mRNA from the transforming segment of the adenovirus 2 genome in productively infected and transformed cells. - Chinnadurai, G (1976)
We have identified two mRNA species transcribed from the adenovirus 2 genome section (HindIII-G fragment) believed to harbor genes for initiation and maintenance of cell transformation. The HindIII-G fragment occupies the left 7.5% of the genome and is transcribed from left to right [poly(U:G) r strand]. Poly(A)-terminated labeled mRNA was isolated from polyribosomes of adenovirus 2 early infected KB cells and from the transformed cell line 8617, hybridization purified using the HindIII-G fragment, and electrophoresed on formamide-polyacrylamide gels. Viral mRNA's of 24S (1.2 X 10(6) daltons) and 14S (4.5 X 10(5) daltons) were isolated from early infected cells and of 22S (1.0 X 10(6) daltons) and 14S from 8617 cells. Hybridization competition indicated that HindIII-G-specific mRNA was present in the polysomes at one-sixth the concentration late after infection as compared with early, indicating that the proteins coded by the transforming segment may be synthesized at reduced amounts during late stages. Only 1/10 the amount of RNA labeled late annealed to the G fragment as compared with that labeled early (per weight of RNA). Thus, synthesis of transforming gene mRNA is probably "turned off" late after infection. Both 24S (22S) and 14S mRNA's from infected and 8617 cells were complementary to the Hpa I-E fragment (left 4.1% of genome). The Hpa I-E fragment is too small to encode 24S and 14S species, which implies that the 5'-terminal regions of both species are coded by the same DNA sequences.